Study on pyrexia in pregnancy and labour with special emphasis on fetomaternal outcome - Sultan, Shabana; Parihar, Reena; Badkur, Poorva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pyrexia in pregnancy is a very common clinical problem worldwide. Fever during pregnancy causes significant maternal and fetal complications. Fetus being an integral part of the feto-maternal unit and pregnancy involving numerous physiological changes and adaptations, pyrexia during the pregnancy affects both the mother and her foetus adversely. Effect of pyrexia on pregnancy depends on the extent of the rise in the temperature. Methods: This is a prospective observational hospital-based study conducted over a period of 1 year from march 2018 to February 2019 Department of Obstetrics and Gynaecology, Sultania Zanana Hospital, Gandhi Medical College, Bhopal. Results: Total no. of antenatal admission in Hospital during study period were 15354. Total 306 cases of pyrexia in pregnancy were found during the study period. Incidence of pyrexia in pregnancy in our study during study period was found 2%. Conclusions: The present study has demonstrated a need for multidisciplinary approach in cases of pregnancy complicated with pyrexia and also higher risk of maternal morbidity and mortality in un-booked patients. We found that pregnancy outcomes were good in booked cases with regular checkup. Early detection and management of patients with pyrexia can certainly help to improve maternal and fetal outcome. This also shows that multidisciplinary approach should extent throughout antenatal, intra-partum and postpartum period.